1976
DOI: 10.1288/00005537-197606000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative chylous fistula prevention and management

Abstract: Postoperative chylous fistulas occur as a complication in 1-2% of all radical neck dissections. Twelve cases are reviewed herein. Chylous fistulas are more common with left neck dissections, but 25% occurred on the right side in this series. An intraoperative chylous fistula was recognized and treated in 75% of the cases which later developed a postoperative fistula. Postoperative fistulas may be divided into two groups: minor fistulas may be treated with pressure dressings and repeated aspirations; fistulas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
2
14

Year Published

1986
1986
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(194 citation statements)
references
References 5 publications
5
173
2
14
Order By: Relevance
“…The most risky procedure is ND, in particular radical ones which is accompanied by chylorrhoea in 1-2%, in 75% on the left [1,2]. Also risky is total thyroidectomy [3], subclavian vein cannulation or injury.…”
Section: Discussionmentioning
confidence: 99%
“…The most risky procedure is ND, in particular radical ones which is accompanied by chylorrhoea in 1-2%, in 75% on the left [1,2]. Also risky is total thyroidectomy [3], subclavian vein cannulation or injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to distinguish the patient with hypocalcaemia whose serum calcium can be normal occasionally from the entity that has surfaced more recently in which the serum calcium is always normal. [12][13][14][15] The old literature, in fact, described some cohorts as "normocalcemic", while more careful inspection has shown that these patients were intermittently normocalcemic. [16][17][18][19][20] The incidence of permanent hypocalcaemia which required calcium supplementation was more accurate with serial calcium estimation than the intact parathyroid hormone (iPTH) levels obtained after total thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed surgery can be however complicated by the granulation, adhesion and make the identification of the structures very difficult. Crumley and Smith recommended 500 ml/24h for more than 4 days to be an indication for surgery (16) while Spiro set the borderline at 600 ml (17). Recently thoracoscopic management of cervical thoracic duct injuries has been suggested though its role is still to be evaluated (9).…”
Section: Treatmentmentioning
confidence: 99%